الرواة الذين ضعفهم النسائي في كتابه "الضعفاء والمتروكين" وأخرج لهم البخاري في صحيحه: دراسة نقدية - محمد، منى محمود إبراهيم (جامعة الأزهر - كلية أصول الدين والدعوة بالزقازيق, 2020)
تناولت هذه الدراسة الرواة الذين ضعفهم الإمام النسائي في كتابه (الضعفاء والمتروكين) وأخرج لهم الإمام البخاري في صحيحه. وكان الهدف منه الدفاع عن صحيح البخاري ضد الشبهة التي أثيرت حوله في الآونة الأخيرة من إخراجه لرواة ضعفهم بعض أئمة الجرح والتعديل، وتكلمت في هذا البحث على الإمام النسائي وكتابه الضعفاء والمتروكين ومنهجه فيه، كما رتبت في بحثي الرواة الذين ضعفهم الإمام النسائي في كتابه، وأخرج لهم البخاري في صحيحه على مراتب التجريح من الأعلى (متروك) إلى الأدنى (ليس بالقوي) وعرضت أقوال النقاد في كل راو، ودرست الأقوال دراسة نقدية ثم بينت الرأي الراجح في كل راو، وذكرت من احتج به البخاري في صحيحه، ومن أخرج له اعتبارا، هذا وقد بلغ عدد الرواة اثنا عشر راويا، وختمت البحث بخاتمة اشتملت على أهم النتائج والتوصيات.
This study addressed the narrators weakened by Imam Al-Nasai in his book Imam (Al-Doafaa Wel Matrokeen) and to whom Imam Al- Bukhari directed in his Sahih. The aim was to defend Sahih Al-Bukhari against the suspicion raised around him recently on his direction for narrators weakened by some imams of vouching and discrediting. I spoke in this research about Imam Al-Nasai and his book (Al Doafaa Wel Matrokeen) and his approach in it. And I arranged in my research the narrators weakened by Imam Al-Nasai in his book, and for whom Imam Al Bukhari directed in his Sahih on vouching levels from the top (abandoned) to the minimum (not strong). In addition, I presented the sayings of critics in each narrator and investigated the sayings critically, and then I showed the correct opinion in every narrator. I mentioned the persons invoked by Bukhari in his Saheeh, and to whom he directed as a consideration. The number of narrators were twelve. I concluded the research with a conclusion that included the most important findings and recommendations.
Keywords: علوم الحديث -- علم رجال الحديث -- كتاب "الضعفاء والمتروكين" -- النسائى، أحمد بن شعيب بن على بن سنان، ت. 915 م